2014
DOI: 10.1055/s-0034-1366747
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Transvaginal Ultrasound Applying Elastography for Identifying Deep Infiltrating Endometriosis – A Feasibility Study

Abstract: The ratio of strain values between two ROIs in the Douglas' s cul-de-sac is associated with the presence of an endometriotic lesion. In the future, these findings could allow for a more detailed pre-surgical evaluation and possibly serve as a novel diagnostic tool for predicting deep infiltrating endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
15
1
1
Order By: Relevance
“…Recently our group assessed deep infiltrating endometriosis using transvaginal elastography. Schiffmann et al showed that the strain ratio between two ROIs in the Douglas's cul-de-sac is associated with the presence of an endometriotic lesion [21].…”
Section: Resultsmentioning
confidence: 99%
“…Recently our group assessed deep infiltrating endometriosis using transvaginal elastography. Schiffmann et al showed that the strain ratio between two ROIs in the Douglas's cul-de-sac is associated with the presence of an endometriotic lesion [21].…”
Section: Resultsmentioning
confidence: 99%
“…Limited data are available on the usefulness of transvaginal elastography in the diagnosis of DIE. DIE nodules usually demonstrate high stiffness on elastography (Figure S20).…”
Section: Other Ultrasound Techniquesmentioning
confidence: 99%
“…45 Other variations of 3D pelvic US, such as introital 3D sonography, 3D rectosonography, and TV elastography have not been demonstrated to outperform 2D US in the detection or characterization of DE. [46][47][48]…”
Section: D Tvsmentioning
confidence: 99%